Jact: A Playground Tool for Comparison of JavaScript Frameworks - Nakajima, Nozomi; Matsumoto, Shinsuke; Kusumoto, Shinji (Proceedings / Asia Pacific Software Engineering Conference, 2019)
Comparing and selecting the most appropriate JavaScript Framework (JSF) is an important activity for web application development. However, it is difficult to collect much information for comparison of JSFs. In this paper, we present a playground tool named Jact to support comprehension of individual JSF characteristics. By the concept of playground, users can freely run, edit, and share source code in their web browsers. Based on the concept, Jact enables developers to compare source codes and runtime performances of each JSF based on typical tasks in web development. Task-based comparison is useful for understanding the feature of each JSF. Furthermore, developers can submit tasks and source code which uses a specific JSF. By sharing tasks and source code written by not only administrators but also developers, Jact can continuously provide information relating to JSF, which includes benchmark and API usage. In order to evaluate the effectiveness of Jact, we conducted a subject experiment with 13 participants. Jact is currently available at http://13.231.18.92.